Accelerator: an intent-based intelligent resource-slicing scheme for SFC-based 6G application execution over SDN- and NFV-empowered zero-touch network - Chowdhury, Mahfuzulhoq (Frontiers in Communications and Networks, 2024)
Zero-touch networks can provide autonomous network solutions by integrating software-based solutions for various emerging 5G and 6G applications. The current literature did not provide any suitable end-to-end network management and resourceslicing solutions for service function chaining (SFC) and user intent-based (time and cost preference) 6G/non-6G application execution over zero-touch networks enabled by mobile edge computing (MEC), network function virtualization (NFV), and software-defined networking (SDN). To tackle these challenges, this paper initiates an end-to-end network management and user intent-aware intelligent network resource slicing scheme for SFCbased 6G/non-6G application execution over zero-touch networks, taking into account various virtual and physical resources, task workloads, service requirements, and task numbers. The results depicted that at least 25.27% average task implementation delay gain, 6.15% energy gain, and 11.52% service monetary gain are realized in the proposed scheme over the compared schemes.